Learning by Striking: Estimates of the Teetotaler Effect - Schnell, John F.; Gramm, Cynthia L. (Journal of Labor Economics, 1987)
We hypothesize that past strike experience will have a negative or "teetotaler" effect on a collective bargaining unit's propensity to strike in future negotiations, other things being equal. We test this using a unique micro-level sample comprising four consecutive negotiations by 147 bargaining units in U.S. manufacturing industries, controlling for observable and unobservable differences among bargaining pairs in the propensity to strike. Our results are consistent with the view that the experience of striking is, indeed, sobering: lagged strike experience variables have a significantly negative effect on the propensity to strike in the current negotiation.